THE FACTORS THAT INFLUENCE MALAYSIAN TEENAGERS’ FAST FOOD PURCHASE INTENTION - Khoo Jiun Lun; Chan Wei Keat; So Soon Kiat; Theah Wan Ying; Caroline Geetha (Malaysian Journal of Business and Economics (MJBE), 2021)
The study aims to ascertain the factors that influence Malaysian teenagers’ fast food purchase intention. The theory used in the study is Theory of planned behaviour followed by dependent variable for this study is the intention of teenagers to buy fast food and independent variables for this study are convenience, food and service quality, brand quality, and restaurant environment to achieve study’s objectives. A website-based questionnaire study was conducted in Malaysia and a total of 30 respondents were collected. The respondents were chosen using non-probability sampling. Statistical Package for Social Science (SPSS) v27 was used to analyse the data for this research. The evaluation of the data for this research was based on factor analysis, reliability analysis, descriptive analysis, and regression analysis. Malaysian teenagers were found to stress more on the convenience aspect in forming their attitude as well as brand quality, restaurant environment and food and service quality to form purchase intention. The 3 factors that are significant in determining the changes in teenager’s purchase intentions of fast food are convenience, food and service quality and brand quality, making restaurant environment is the not significant factor. The findings help fast food marketing practitioners and the government in planning for more effective societal marketing strategies to promote a healthy diet among Malaysian teenagers.